2010
DOI: 10.1371/journal.pgen.1001159
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan Extension by Preserving Proliferative Homeostasis in Drosophila

Abstract: Regenerative processes are critical to maintain tissue homeostasis in high-turnover tissues. At the same time, proliferation of stem and progenitor cells has to be carefully controlled to prevent hyper-proliferative diseases. Mechanisms that ensure this balance, thus promoting proliferative homeostasis, are expected to be critical for longevity in metazoans. The intestinal epithelium of Drosophila provides an accessible model in which to test this prediction. In aging flies, the intestinal epithelium degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
437
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(462 citation statements)
references
References 92 publications
(128 reference statements)
23
437
0
2
Order By: Relevance
“…Structural and functional impairments within the intestinal epithelium have been reported in aged mammals (9) and Drosophila (10-13). Moreover, we (13) and others (14)(15)(16) have shown that the intestine represents an important target organ with respect to genetic interventions that promote longevity in both C. elegans and Drosophila (17). One interpretation of these findings is that maintaining intestinal integrity is an important determinant of health and viability at the organismal level; however, given that most assays of intestinal homeostasis are based on imaging techniques that require killing the flies (10-12), it has not been possible to determine how the onset of intestinal degeneration in individual flies relates to other aspects of aging and/or subsequent mortality.…”
mentioning
confidence: 72%
“…Structural and functional impairments within the intestinal epithelium have been reported in aged mammals (9) and Drosophila (10-13). Moreover, we (13) and others (14)(15)(16) have shown that the intestine represents an important target organ with respect to genetic interventions that promote longevity in both C. elegans and Drosophila (17). One interpretation of these findings is that maintaining intestinal integrity is an important determinant of health and viability at the organismal level; however, given that most assays of intestinal homeostasis are based on imaging techniques that require killing the flies (10-12), it has not been possible to determine how the onset of intestinal degeneration in individual flies relates to other aspects of aging and/or subsequent mortality.…”
mentioning
confidence: 72%
“…It will be interesting to determine whether the modulation of specific chromatin regulators can restore the proliferative and multipotential properties of stem cells and thereby ameliorate age-dependent tissue decline. Moreover, the relationship between stem cell function and organismal longevity has yet to be rigorously addressed in mammals, although the importance of specific tissue-stem cells (gut stem cells) in organismal longevity has been revealed in invertebrates (Biteau et al, 2010). As the mechanisms underlying agedependent stem cell decline are better understood, studying the effects of manipulating stem cell function on overall organismal lifespan and healthspan will be an attainable goal.…”
Section: Future Directionsmentioning
confidence: 99%
“…JNK signalling has been shown to counteract the effects of ROS and antagonize Insulin/IGF signalling (IIS) leading to extension of lifespan (Wang et al, 2003) (Wang et al, 2005). Interestingly, balanced levels of JNK or IIS in ISCs contribute favourably to intestinal homeostasis and also increase animal lifespan (Biteau et al, 2010). A similar outcome has been observed upon reduction of Myc-dependent ISC proliferation in hyperplastic fly midguts (Cordero et al, 2012a).…”
Section: Ageing and Intestinal Stem Cell Homeostasismentioning
confidence: 85%